Pengenalan Website Lapak Desa Dan Cara Memasarkan Produk UMKM Secara Online Di Desa Sambi Rejo Timur Deli Serdang Sumatera Utara - Husni Lubis; Ihsan Lubis; Halimatussa’diah; Maxi. L Hutahaean; Marcho M Hutahaean; Ahmad Daffa; Yuli Artika; Salsabila (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Digital marketing is one method used by business actors to introduce their products and services to the public. Apart from that, digital marketing can also be used as a transaction medium between sellers and buyers. With digital marketing, product marketing reach can be wider and reach more people. Customer and marketing costs can be reduced and made more efficient. Village Stalls is one of the service team's proposals to help business actors market  their products. In order to further promote the website, it is necessary to introduce business actors regarding the use of the website. Furthermore, the team also helps entrepreneurs or administrators with registration and provides an introduction to the features they have. From this activity, it is hoped that the marketing of business actors' products will be broader and can help increase the level of income of the people in the village.